Isotope gastric emptying tests in clinical practice: expectation, outcome, and utility. Issue 7 (July 1993) - Galil, M A; Critchley, M; Mackie, C R
Abstract : Tests of gastric emptying with modern scintigraphic methods are recommended in the clinical management of gastric disorders. An audit of 472 gastric emptying tests carried out over a 10 year period was performed to discover the reasons for requests from consultant clinicians, their anticipation of the results of tests, and the influence of the results upon the subsequent management of their patients. Excluding control (n = 47) and research (n = 50) studies, there were 375 clinical referrals that could be grouped under the headings: non-ulcer dyspepsia (n = 72), suspected diabetic gastroparesis (n = 18), peptic ulcer (n = 15), suspected delayed gastric emptying after surgery (n = 154), dumping and diarrhoea (= 107), and other indications (n = 9). Although the results were abnormal for 55 (48%) of the 'medical' patients, they did not seem to influence clinical management. Delayed gastric emptying after surgery was confirmed in only 20% of patients referred with this clinical diagnosis. Conversely, most (79%) o the patients referred with dumping and diarrhoea exhibited abnormally rapid emptying. Isotope gastric emptying studies may be useful in clinical practice. The results are often at variance with the clinical diagnosis. Clinicians must take into account the nature of the test meal used when results are correlated with clinical features.